The Bear Grylls Adventure. Book 5, The River Challenge [anglicky] - Grylls, Bear (Bear Grylls Ventures, 2019)
The fifth adventure in the fun new 12-book collectible series for young readers from survival expert and Chief Scout BEAR GRYLLS.